2009
DOI: 10.1002/cbdv.200800105
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of Aedes aegypti and Culex quinquefasciatus Larvae to Gedunin‐Related Limonoids

Abstract: The major non-azadirachtin limonoids such as gedunin (1), epoxyazadiradione (3), nimbocinol (4), and nimolicinol (5) from Azadirachta indica A. Juss ('neem') and their derivatives were evaluated for their toxic action against fourth instar larvae of Aedes aegypti L. and Culex quinquefasciatus Say. Gedunin exhibited 100% toxic action against both the mosquito larvae at 50 and 10 ppm. Epoxyazadiradione and epoxynimolicinol also showed significant toxicities (> or =50%) against larvae of both mosquito species at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Quantitative molecular calculations of the structure–activity relationship indicated that the insecticidal activity of azadirachtins was directly proportional to the polarity of ring A, the steric requirements of the substituents at C-7, and the rotations around the single bond between C-8 and C-14 . The potent larvicidal activity of gedunin ( 416 ) indicated that the epoxidation and expansion of ring D had a favorable effect on this activity, as was also the case for the CC bond in the ring A in nimbocinol ( 13 ) and nimolicinol ( 451 ) …”
Section: Biological Activities Of Meliaceous Limonoidsmentioning
confidence: 98%
“…Quantitative molecular calculations of the structure–activity relationship indicated that the insecticidal activity of azadirachtins was directly proportional to the polarity of ring A, the steric requirements of the substituents at C-7, and the rotations around the single bond between C-8 and C-14 . The potent larvicidal activity of gedunin ( 416 ) indicated that the epoxidation and expansion of ring D had a favorable effect on this activity, as was also the case for the CC bond in the ring A in nimbocinol ( 13 ) and nimolicinol ( 451 ) …”
Section: Biological Activities Of Meliaceous Limonoidsmentioning
confidence: 98%
“…Twentyseven compounds identifi ed in nonpolar to less polar fractions of the ethanolic extract of fresh neem fruit showed pesticidal activity determined by WHO method against Anopheles stephensi (Siddiqui et al 2004b ). Gedunin exhibited 100 % toxic action against the fourth instar larvae of Aedes aegypti and Culex quinquefasciatus at 50 and 10 ppm (Gurulingappa et al 2009 ). Epoxyazadiradione and epoxynimolicinol also showed signifi cant toxicities (≥50 %) against larvae of both mosquito species at 50 ppm.…”
Section: Insect Growth-regulating/larvicidal Activitiesmentioning
confidence: 98%
“…Finally, elimination of the TES substituent of 314 followed by a Ley oxidation afforded (�)-315 (17% over 3 steps) (Scheme 47). [104b] In 1960, Taylor et al demonstrated the extraction of a novel tetranortriterpenoid from the West African timber Entandrophragma angolense that was known as gedunin (322). [314] Gedunin showed antifungal, [315] antimalarial, [316] allergic response, [317] anticancer, [318] peptic ulcer, [319] antifilarial, [320] eryptosis, [321] and also insecticidal [322] properties.…”
Section: Tetranortriterpenoidsmentioning
confidence: 99%